Nonrealistic American Plays: Ties Between Continental and American Expressionistic Drama - Alyahya, Rimah (Richtmann Publishing, 2012)
In order to establish a concrete basis for the frequently mentioned but superficially investigated ties between Continental andAmerican Expressionist drama, this study endeavors not only to examine the expressionistic elements in native plays but also todetermine the extent to which American playwrights were inspired by the works of Continental-chiefly German-Expressionists. This studyfocuses on the nonrealistic dramaturgy of Georg Kaiser, Walter Hasenclever, and other Continental Expressionists, which inspired manyAmerican playwrights such as Tennessee Williams, Arthur Miller, Elmer Rice, and John Howard Lawson. It shows their attempts to fuserealistic and expressionistic elements into esthetically satisfying dramatic works and how American Expressionism has tended to followmore the examples set by the German Expressionists than that by Strindberg, in whose